Anti-inflammatory cytokines in autism spectrum disorders: A systematic review and meta-analysis. (November 2019) - Saghazadeh, Amene; Ataeinia, Bahar; Keynejad, Kimia; Abdolalizadeh, Amirhussein; Hirbod-Mobarakeh, Armin; Rezaei, Nima
Highlights: In the search for the causes of autism, inflammatory markers have emerged as potential candidates. Studies have provided inconsistent results on altered levels of cytokine in patients with autism. Meta-analyses show lower levels of IL-10 and IL-1Ra in autistic patients compared with controls. Meta-analysis shows slightly higher levels of serum IL-5 in patients with autism. Meta-regression shows that latitude, age, and gender influence alteration of IL-5, -10, and -1Ra in autism. Abstract: Background: In the search for the causes of autism spectrum disorders (ASD), inflammatory markers have emerged as potential candidates. The present meta-analysis was performed on studies examining circulating concentrations of anti-inflammatory cytokines in people with ASD compared with control subjects without ASD. Methods: We identified potentially eligible studies by systematically searching electronic databases from inception to February 2018. Results: Twenty-five studies with a total of 1754 participants (1022 patients with ASD and 732 control subjects) were included in the mate-analysis; 4 for interferon (IFN)-α, 9 for interleukin (IL)-1 receptor antagonist (Ra), 9 for IL-4, 6 for IL-5, 3 for IL-9, 14 for IL-10, 7 for IL-13, and 6 for transforming growth factor (TGF)-β. We found a moderate decrease in plasma levels of IL-10 (SMD = −0.59) and a small decrease in serum levels of IL-1Ra (SMD = −0.25) in patients with ASD. On the contrary, serum IL-5 levels were slightly increased (SMD = 0.26) in these patients. We conducted meta-regression analyses to investigate the possible effect of moderatos on the effect size (ES) of difference in mean levels of IL-10. Difference in the mean age between patients and controls showed a negative influence on the ES and was able to explain about 0.4 of total between-study variance. In contrast, latitude exerted a positive effect on the ES and explained a lower proportion (0.1) of total between-study variance. Conclusions: This meta-analysis provides evidence for the lower concentration of anti-inflammatory cytokines IL-10 and IL-1Ra in autistic patients compared with control subjects. Also, meta-regression analyses point to the interaction of latitude, age, and gender with peripheral alterations of associated anti-inflammatory cytokines.